Evaluation of Intracranial Structures of Fetuses With Congenital Heart Defects. (10th July 2022) - Turgut, Ezgi; Özdemir, Halis; Turan, Gokce; Karcaaltıncaba, Deniz; Bayram, Merih
Abstract : Objectives: We classified congenital heart defects (CHDs) according to cerebral blood flow oxygenation and aimed to evaluate the effect on the size of brain structures in these fetuses. Methods: The study which was designed retrospectively, included 28 patients with fetal CHDs and 76 patients without fetal anomalies. Results: The width and length of the cavum septum pellucidum significantly increased in the CHD group ( P  = .002, P  = .004). The biparietal diameter and z scores were significantly lower in the single ventricle (SV) ( P  = .006, P  = .019), and the head circumference (HC) and z scores were significantly lower in the transposition of great arteries (TGA) ( P  = .013, P  = .038). The transverse cerebellar diameter, the cerebellar HC and the cerebellar hemisphere area values were lower in the SV ( P  = .005, P  = .017, P  = .044). Conclusions: Brain structure changes are more pronounced in groups with low cerebral oxygenation, especially in the SV and the TGA. Abstract : Access the CME test here and search by article title.